Taxonomy, biostratigraphy, and phylogeny of Globigerinatheka and Orbulinoides - I. Premoli Silva; B. S. Wade; P. N. Pearson (Cushman Foundation for Foraminiferal Research, 2006)
Globigerinathekids were abundant and diverse through the middle and upper Eocene. Globigerinatheka comprises 11 species, namely G. barri Brönnimann, G. curryi Proto Decima and Bolli, G. euganea Proto Decima and Bolli, G. index (Finlay), G. korotkovi (Keller), G. kugleri (Bolli, Loeblich and Tappan), G. luterbacheri Bolli, G. mexicana (Cushman), G. semiinvoluta (Keijzer), G. subconglobata (Shutskaya), and G. tropicalis (Blow and Banner). Orbulinoides is a monotypic genus comprised solely of the short ranging species O. beckmanni (Saito). In this paper the taxonomy, phylogeny, and biostratigraphy of Globigerinatheka Brönnimann, 1952 (emended Proto Decima and Bolli, 1970) and Orbulinoides Cordey, 1968 (emended Proto Decima and Bolli, 1970) are reviewed.